Strategies for Ratifying Marriage Agreements to Avoid Partnership Liabilities - Almaududi Almaududi; Shafira Hijriya (Jurnal Wawasan Yuridika, 2023)
This research aims to analyze the regulations and strategies for validating marriage agreements. This normative juridical research prioritizes secondary data as primary, secondary, and tertiary legal materials. Data was collected through document and literature studies and then analyzed qualitatively using a statutory and historical approach. The research findings indicate that the development of marriage agreement regulation can be categorized into three phases: before the enactment of Marriage Law, after the enactment, and after the Constitutional Court Decision No. 69/PUU-XIX/2016. Moreover, regulation remains unclear and has not been followed with legislation, giving rise to "strategies" to avoid partnership liabilities. One party may create a marriage agreement after entering into Marriage, and subsequently, that party only validates the marriage agreement before a notary (waarmerking).